Effect of nano-CaCO3 on compressive strength development of high volume fly ash mortars and concretes - Supit, S.; Shaikh, Faiz (Japan Concrete Institute, 2014)
This paper presents the experimental results on the effect of nano-CaCO3 on compressive strength development of mortars and concretes containing high volume fly ash (HVFA). The effect of various nano-CaCO3 contents such as 1, 2, 3and 4% (wt.%) as partial replacement of cement on the compressive strength of mortars are evaluated in the first part. The nano-CaCO3 content which exhibited the highest compressive strength above is used in high volume fly ash mortars and concretes containing 40% and 60% class F fly ash. The results show that among four different nano-CaCO3contents, the addition of 1% nano-CaCO3 increased the compressive strength of mortars and concretes. The addition of1% nano-CaCO3 also increases the early age and 28 days compressive strengths of HVFA mortars and concretes. The X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) analysis results also support the above findings.